A comparative study of amyloid-beta (1-42) as a cofactor for plasminogen activation by vampire bat plasminogen activator and recombinant human tissue-type plasminogen activator - Kruithof, Egbert K. O.; Schleuning, Wolf-Dieter (Thrombosis and Haemostasis, 2004)
The activity of both human tissue-type plasminogen activator (t-PA) and the PA from the saliva of the vampire bat, Desmodus rotundus, (DSPA) is critically dependent on the presence of a cofactor. The most efficient cofactor for both PAs is fibrin, but fibrinogen and amyloid beta peptides also have cofactor activities for human t-PA. Compared to t-PA, DSPA has a more stringent requirement for fibrin as a cofactor. The present study was undertaken to compare cofactor activities of amyloid beta 1-42 (Aβ1-42) for plasminogen activation by DSPA-α1 or by t-PA. The two PAs were incubated with different concentrations of glu-plasminogen, a chromogenic substrate for plasmin and 100 µg mL-1 of Aβ1-42, fibrinogen or fibrin as cofactor. Using the kinetic parameters directly determined from the chromogenic substrate conversion curves, we derived the relative efficacies of DSPA or t-PA in the presence of cofactor at the physiological plasminogen concentration of 2 µM. In the presence of fibrin, the activity of DSPA was comparable to that of t-PA and 23,270-fold higher than its activity without cofactor, whereas fibrin induced only a 248-fold increase in t-PA activity. The activity of DSPA with Aβ1-42 or fibrinogen as cofactor was 485-fold lower than its activity in the presence of fibrin, while for t-PA this difference was only 26-fold. The much lower activity of DSPA as compared to t-PA with Aβ1-42 or fibrinogen might lead to fewer side effects when used for the thrombolytic therapy of stroke.
Keywords: Plasminogen activator; fibrinogen; fibrin; amyloid beta; cofactor